Transformation Of Islamic Religious Education (PAI) Learning With A Deep Learning Approach - Yulianto, Eko; Wantini, Wantini; Khoirudin, Azaki (Journal of Indonesian Progressive Education, 2025)
This study aims to analyze the learning transformation of Islamic Religious Education (PAI) through the Deep Learning approach at the Luqman Al Hakim Integrated Islamic Elementary School Yogyakarta. This approach is implemented as a solution to create a learned, meaningful, and enjoyable learning experience for students. This qualitative research uses a case study design with data collection techniques through triangulation involving school principals, PAI teachers, and students in grades III and VI. The research instruments included in-depth interviews, observations, and documentation studies on the Fifth Edition of JSIT Indonesia's Quality Standards, School Operational Curriculum (KOS), and In-Depth Learning Plans (RPM). Data analysis is carried out through the stages of reduction, data presentation, and conclusion drawn. The results of the study show that SDIT Luqman Al Hakim Yogyakarta has taken transformative steps by implementing a Deep Learning approach in stages  in PAI subjects. Through careful planning, participatory implementation, and authentic process-based evaluation.  This research makes a theoretical and practical contribution as well as a reference in the development of transformative learning strategies in elementary schools.